Localized transient lingual papillitis. - Milano, A. (European Journal of Pediatric Dermatology, 2017)
Transient lingual papillitis is characterized by inflammatory enlargement of one or more lingual papillae, acute onset, pain and spontaneous regression in days. There is a localized variant that, as in our case, affects few papillae of the dorsal surface of the tongue, tip or lateral surfaces of the tongue and a generalized variant that affects 3-4 year old children, and immediately afterwards manifests itself in other members of the family: this form is called eruptive familial lingual papillitis. The affected papillae may be of normal, whitish or yellowish color. The severity of the symptomatology is variable and can be associated with intense burning, sialorrhea, adenopathy, fever. Histology shows a nonspecific picture of minimal intraepithelial spongiosis and polymorphonuclear infiltrate in the chorion.